Taken - Bloor, Edward, 1950- (Alfred A. Knopf, 2007)
In 2036 kidnapping rich children has become an industry, but when thirteen-year-old Charity Meyers is taken and held for ransom, she soon discovers that this particular kidnapping is not what it seems.